Specifics of Welded Joint Destruction Obtained by Friction Stir Welding at Strain; Applied Mechanics and Materials; Vol. 756 : Mechanical Engineering, Automation and Control Systems (MEACS2014) - Kolubaev Е. А. Evgeny Aleksandrovich; Sizova O. V. Olga Vladimirovna; Zaikina A.; Levihina A. (Mechanical Engineering, Processing and Surface Engineereng, Metals Treatment, Equipment and Tools, 2015)
Title screen